Evektifitas Model Latihan Rondo Terhadap Kemampuan Passing Futsal pada Siswa Ekstrakurikuler SMA Negeri 11 Makassar - Badaru, Benny; Alim, Bahrul; Alimsyah, Andi Saiful; Zainuddin, M. Said (Prodi Pendidikan Jasmani dan Olahraga, 2026)
Passing ability is one of the fundamental skills in futsal that greatly determines the effectiveness of ball control and the success of game strategies. Based on initial observations in the futsal extracurricular activities of SMA Negeri 11 Makassar, it was found that students' passing ability was still low, characterized by a lack of accuracy, tempo, and consistency of passes. This study aims to analyze the effect of the Rondo training model on improving the passing ability of futsal extracurricular students. This study used a quasi-experimental method with a two-group pretest–posttest design. The study sample consisted of 20 students divided into an experimental group and a control group. The experimental group was given treatment in the form of Rondo training for four weeks with a frequency of three times per week, while the control group underwent conventional futsal training. The research instrument was a futsal passing ability test that covered aspects of accuracy, speed, and passing technique. Data were analyzed using descriptive statistics, normality tests, and paired sample t-tests. The results showed a significant increase in passing ability in the experimental group. The average score increased from 56.25 in the pretest to 65.10 in the posttest, with a t-value of 6.030 and a significance level of 0.000 (p < 0.05). Thus, it can be concluded that the Rondo training model has a significant effect on improving the passing ability of futsal extracurricular students at SMA Negeri 11 Makassar. This training model is recommended as an alternative effective training method in futsal coaching at the school level.